2021
DOI: 10.1007/s11010-021-04110-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanog overexpression on the metastatic potential of a mouse melanoma cell line B16-BL6

Abstract: Nanog, a marker and regulator of the undifferentiated state in embryonic stem cells were anticipated to be an effective enhancer of cancer metastasis. We have developed a Nanog overexpressing mouse melanoma cell line B16-BL6 (BL6). BL6 was well recognized as a cell line with a high metastatic potential. In vitro tests revealed the enhancement of cell proliferation, wound healing activity, and matrix metalloproteinase 9 (MMP9) activity. Nanog-induced up- or down-regulated genes were comprehensively analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In a previous study, we showed that Nanog overexpression caused a decrease in the expression of TGF-β1 in BL6 cells [ 18 ]. Here, we likewise found that the level of TGF-β1 expression in Nanog + F10 cells decreased by 0.37 fold compared to F10 cells ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that Nanog overexpression caused a decrease in the expression of TGF-β1 in BL6 cells [ 18 ]. Here, we likewise found that the level of TGF-β1 expression in Nanog + F10 cells decreased by 0.37 fold compared to F10 cells ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we modified the melanoma cell line B16-BL6 (BL6) to overexpress Nanog , a major factor for maintaining the undifferentiated state of embryonic stem cells, in the expectation that this would increase the metastatic potential of this cell line. The modified BL6 line did indeed show an enhanced level of metastatic potential [ 18 ]. A transcriptome sequencing analysis indicated that transforming growth factor (TGF)-β1 was the only secretory cytokine among the top15 up-regulated and top 16 down-regulated genes after Nanog overexpression in BL6 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptome analysis of mouse melanoma cells was conducted to clarify the differential expression intensities between a cell line, B16-BL6, and its Nanog -overexpressing cell line Nanog + BL6. The up-regulated top-16 genes and down-regulated top15 genes were depicted [ 19 ]. The functional roles of up-regulated top-7 genes and down-regulated top-3 genes are illustrated in Figure 3 A,B, respectively.…”
Section: Nanog Overexpression In Melanomamentioning
confidence: 99%
“…Since the expression level of Tgf-β1 was a controversial matter, it was analyzed at mRNA and protein levels. As a result, its expression was down-regulated at both levels [ 19 ]. Another study conducted elsewhere [ 18 ] demonstrated a conflicting result.…”
Section: Nanog Overexpression In Melanomamentioning
confidence: 99%
See 1 more Smart Citation